ABOUT SOME ISSUES OF THE ACTIVITY OF THE EAEU COURT: A COMPARATIVE LEGAL ANALYSIS - Meghryan, Armen (State and Law, 2024)
Since the establishment of the Eurasian Economic Union, questions related to the activity of the court of this Union have gained great importance and there has been a need to research them, even though there are very few scientific works related to this international court in our domestic legal literature. This article talks about the judicial activity of the Court of the EAEU and the decisions made by it, which are not the source of the Union law, comparing them with the functions of the Court of the European Union. With the help of the method of comparative legal analysis, in this article, a discussion was made about some issues of the provision of advisory opinions by the EAEU Court and the EU Court, the European Court of Human Rights, and the International Court of Justice. In this context, a comparative legal analysis of EAEU and EU courts, including other international courts, will allow to identification of legal issues related to the status and activity of the EAEU court and offer possible options for their solutions. Moreover, such an analysis can be a guide for the contracting parties when discussing the issue of the legal status of the Court of the Union.